Natural Resource Management for Sustainable Agricultural Development: A Study of Agro-ecological Zoning for Rupandehi District - Rai, S.K.; Pandey, S.P. (Journal of the Institute of Agriculture and Animal Science, 2004)
The study was conducted during 1998-2000 to identify, characterize, and utilize the natural resources for developing sustainable agriculture system in Rupandehi district, Nepal by using Geographic Information Systems (GIS). Agro-ecological zones (AEZ) were delineated for the study area, which had the homogeneity in terms of the resources i.e. soil, land use and climate. Various resource themes were mapped and/or generated separately by using geostatistical procedures in GIS environment, which were later overlaid onto each other to develop final AE Zones. Thirteen AEZs were identified for the study area. The highest area of 26.3% falls under the zone "wetland with medium soil and length of growing period (LGP) II" followed next by "upland medium soil and LGP II" (18.2%). The subtropical climate of study area has the thermal suitability for most of the agronomic crops of subtropics except few winter crops. Moisture stored in soil from rainfall is not sufficient for winter crops that have longer growing period and hence supplement irrigation is essential for more production. All of these resource based situation analysis would provide an insight for a systematic way of resource management and utilization for a sustainable and environmentally friendly agricultural system with equal attention to resource base potentials and limitations. J. Inst. Agric. Anim. Sci. 25:23-30 2004